The determinants of live fish consumption frequency in South Korea. (June 2019) - Lee, Min-Kyu; Nam, Jongoh
Abstract: In South Korea, aquaculture producers, fish restaurant operators and the government need detailed information regarding individual-level consumption of live fish. This study aims to identify determinants of live fish consumption frequency. Specifically, by using micro-survey data obtained from interviews of 800 randomly selected households in the South Korean metropolitan cities, an ordered probit model is estimated. Overall, the estimation results reveal that the chosen model is appropriate to analyze consumers' preferences for live fish. The coefficients of residential area, household income, preferences, favorable fish species, the importance of price, and safety are statistically significant at the 10% level. If consumers consider price an important factor, their consumption of live fish may decrease. Moreover, consumers with high satisfaction for safety are more likely to consume live fish more frequently. To increase the consumption of live fish, it is recommended to develop products designed for segmented markets and to promote their functional attributes. This study is expected to provide useful information for designing effective strategies to marketing managers. Graphical abstract: Unlabelled Image Highlights: This study identifies determinants of live fish consumption frequency. To this end, survey of 800 households in South Korea was conducted. An ordered probit model was applied to analyze the preference for live fish. Consumers with high satisfaction for safety consume live fish more frequently.